PENERAPAN KONSEP RELATIONSHIP MARKETING DALAM RISET PAJAK - Susila, Ihwan (Benefit: Jurnal Manajemen dan Bisnis, 2004)
This paper discusses about relationship between sacrifice and motivation in taxpayer. This articlefocus in analysing the impact of sacrifice and service quality to motivation. This impact mediating byservice value. The research model based on relationship marketing. This paper offers a proposition.Sacrifice, service quality, and satisfaction have influences to tax payer motivation.